Análisis de la evaluación del pasto alemán Echinochloa polystachya (H.B.K.) Hicth cultivado en suelo arcilloso bajo cuatro frecuencias de corte - Manrique P. Luis Phanor (Acta Agronómica)
En el experimento realizado en la hacienda Lucerna, Bugalagrande, Colombia, se utilizó un diseño de parcelas completamente al azar, con dos repeticiones para cuatro frecuencias de corte a los 21,35,49 y 63 días. La capacidad de enraizamiento varió entre 97.8 y 99.8% para los cortes realizados a los 21 y 63 días, respectivamente. La altura de las plantas aumentó en relación directa con la frecuencia de los cortes. El porcentaje de macollamiento se incrementó progresivamente con el aumento de las edades de los cortes y el porcentaje de floración se acrecentó sucesivamente para las frecuencias de 49 y 63 días. El promedio de producción de materia verde para las cuatro frecuencias de corte (8.5, 13.5, 19.5, 27.4 t/ha), presentó diferencias altamente significativas. Se presentaron diferencias estadísticas altamente significativas en materia seca (15.9, 23.1, 32.0 y 31.8 %), proteína bruta (13.0, 9.5, 7.1 y 5.2%), digestibilidad in vitro de la materia seca (61.8, 58.9, 56.6 y 54.6%) y digestibilidad in vitro de la materia orgánica (64.8, 61.3, 58.5 y 57.7%). The main objective of this research was to study the agronomic performance and the nutritive value of German grass (Echinochloa polystachya), grown on clayed soil at Lucerna farm, located at Bugalagrande county in Cauca Valley of Colombia. The test was carried out, considering four cutting frequencies, 21,35,49 and 63 days. A complete random designed was utilized, in order to realize the statistical analysis. The analysis of rooting production capacity of the grass shows a variation of 97.8% and 99.8%, considering the cuttings done at 21 and 63 days, respectively. The plants height increase in a direct ratio to cutting frequency. On the other hand, the percent of grass clustering also increase progressively when the of cutting increase, and the percent of flowering also increase for the cutting done at 49 and 63 days. The mean production of green matter was 8.5, 13.5, 19.5 and 27.4 ton/ha, for the different cutting frequencies. These results showed a high significant differences. Concerning to the nutritive value analysis, the results showed a variations with a high significant differences in dry matter as follows 15.9, 23.1, 32.0 and 31.8%; in relation to gross protein, results were 13.0, 9.5, 7.1 and 5.2%; In vitro digestibility of dry matter, the results present the following data 61.8, 58.9, 56.6, 54.6% and finally the in vitro digestibility of the organic matter showed 64.8, 61.3, 58.5 and 57.7%, for the cutting frequencies by 21,55,49 and 63 days, respectively.